Selective Hydrogenation of α, β‐Unsaturated Aldehydes and Ketones by Air‐Stable Ruthenium NNS Complexes. Issue 35 (31st May 2017) - Puylaert, Pim; van Heck, Richard; Fan, Yuting; Spannenberg, Anke; Baumann, Wolfgang; Beller, Matthias; Medlock, Jonathan; Bonrath, Werner; Lefort, Laurent; Hinze, Sandra; de Vries, Johannes G.
Abstract: The selective hydrogenation of the carbonyl functionality of α, β‐unsaturated aldehydes and ketones is catalysed by ruthenium dichloride complexes bearing a tridentate NNS ligand as well as triphenylphosphine. The tridentate ligand backbone is flexible, as evidenced by the equilibrium observed in solution between the cis ‐ and trans ‐isomers of the dichloride precatalysts, as well as crystal structures of several of these complexes. The complexes are activated by base in the presence of hydrogen and readily hydrogenate carbonyl functionalities under mild conditions. Despite the activation by base, side reactions are negligible, even for aldehyde substrates, because of the low amount of base. Thus, the corresponding allylic alcohols can be isolated in very good yields on a 10–25 mmol scale. Turnover numbers up to 200 000 were achieved. Abstract : Cheap yet noble : New, easily prepared tridentate NNS ligands and their ruthenium complexes are described. The complexes are activated by base and selectively catalyse the hydrogenation of carbonyl functionalities in the presence of conjugated carbon–carbon double bonds.